2019
DOI: 10.1371/journal.pone.0210106
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and risk factors for renal disease for patients receiving HIV pre-exposure prophylaxis at an inner metropolitan health service

Abstract: BackgroundPre-exposure prophylaxis (PrEP) with tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) significantly reduces the risk of HIV acquisition. TDF is a known nephrotoxin however, renal dysfunction from TDF is mostly reversible following discontinuation.AimsTo describe the renal function, risk factors for renal disease and associated clinical testing practices in a cohort of PrEP patients.MethodsA retrospective review was conducted of all PrEP patients commenced on TDF/FTC at an inner metropolitan sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
3
15
0
2
Order By: Relevance
“…Grinsztejn et al [ 4 ] showed that PrEP was feasible and safe, with very few adverse events sufficiently severe to lead to exclusion of participants due to a decline in renal function. Despite the lack of clinical manifestations, a significant and sustained variation in eGFR was recorded, similar to that reported in other studies regarding PrEP users [ 8 , 20 , 21 ]. In our study, eGFR reached its highest variation as early as week 4 of follow-up after the start of TDF/FTC-based PrEP, when compared to the baseline visit, and was maintained until the week 48 follow-up visit.…”
Section: Discussionsupporting
confidence: 87%
“…Grinsztejn et al [ 4 ] showed that PrEP was feasible and safe, with very few adverse events sufficiently severe to lead to exclusion of participants due to a decline in renal function. Despite the lack of clinical manifestations, a significant and sustained variation in eGFR was recorded, similar to that reported in other studies regarding PrEP users [ 8 , 20 , 21 ]. In our study, eGFR reached its highest variation as early as week 4 of follow-up after the start of TDF/FTC-based PrEP, when compared to the baseline visit, and was maintained until the week 48 follow-up visit.…”
Section: Discussionsupporting
confidence: 87%
“…In the Discover trial, the mean reduction in creatinine clearance at one year in the TDF/FTC arm was −2.30 mL/min . The mean eGFR reduction was even more pronounced in the EPIC – NSW study (−4.5 mL/min/1.73 m 2 per year) .…”
Section: Discussionmentioning
confidence: 85%
“…In the Discover trial, the mean reduction in creatinine clearance at one year in the TDF/FTC arm was À2.30 mL/min [26]. The mean eGFR reduction was even more pronounced in the EPIC -NSW study (À4.5 mL/min/1.73 m 2 per year) [27]. The overall reduction and intermittent exposure to TDF/ FTC in our study as compared to a daily regimen, may explain the better renal safety of on-demand PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…We also only had to discontinue PrEP for three patients for medicationrelated kidney issues, which matches the rates of discontinuation for renal toxicity found in the initial and larger physician-run trials. [18][19][20] This point about discontinuation is important because it helps validate our creatinine monitoring pathway, 7 which could facilitate greater taskshifting to healthcare providers who may be less familiar with PrEP and renal function monitoring; for example, RNs or physicians who have not worked with renal function testing ever or in many years. This finding about our participants is also important because it supports previous analyses that found PrEP-RN to be a more cost-effective way to delivery PrEP.…”
Section: Discussionmentioning
confidence: 99%